A mirror of political ideology: undergraduates’ attitudinal drivers on implemented campus carry - Butters, Albion M.; Kestilä-Kekkonen, Elina; Ruoppila, Sampo (Frontiers in Political Science, 2024)
Campus carry, which allows individuals possessing a license (or, more recently, a right) to carry concealed firearms to legally bring them onto public university campuses, was implemented in Texas in 2016, but it has remained a contested issue at The University of Texas at Austin. Based on a survey of undergraduates (N = 1,204) conducted in spring 2019, this paper examines predictors of support and opposition for the policy, including gender, ethnicity, socioeconomic background, political affiliation and ideology, length of time lived in Texas, and pro-gun legal attitudes. The study found that attitudes were profoundly driven by the political views of the students. Their gender and pro-gun legal attitudes also had significance, whereas many other variables identified by previous research did not. The study contributes to an understanding of campus carry attitudes in situations where it is not only planned or a distant hypothetical but already in effect and impacting students’ lives.